Investigação da ação disruptora da deltametrina sobre a tireoide e função hipofisária de ratos (Gerações F1 E F2) - Santos, Julio Cezar dos (2018)
Little is known about chronic exposure to pyrethroids; however, contact with this type of substance is common and has often been found in breast milk and urine, in addition to environmental detections that have sometimes been related to diverse biological changes. The present study aims to evaluate the possible disruptive actions of deltamethrin in low doses on the thyroid, a hyposal function in the development in transgenerations of rats. For this, 6 non-consanguine adult, Wistar albino rats were used, provided by the Central Vivarium of the State University of the West of Paraná (UNIOESTE). All the experimental procedures were followed the protocol evaluated and approved by the Committee of Ethics in the Use of Animals of the State University of the West of Paraná (CEUA / UNIOESTE). The treatment group received a daily intraperitoneal injection of deltamethrin at the concentration of 0.01 mg.kg-1 of body weight between the 8th and 14th day of pregnancy, the control group received canola oil. Next generations (F1 and F2) did not receive treatment and were evaluated for growth and development, by birth weight, Lee index and weight at euthanasia. After euthanasia, the pituitary gland was isolated and weighted. A positive correlation was observed between weight variation throughout pregnancy and the number of pups born. There was no difference between the treatment and control groups in the birth weight of first generation rats (F1). The birth weight of the 2nd generation (F2) rats from the treated rats was lower in comparison with the weight of those from the control rats. When assessing weight, Lee's index and pituitary weight at euthanasia, there were no statistical differences between control and treatment. Females had larger pituitary glands when compared to males. We concluded that deltamethrin interferes with the birth weight of rats and this interference follows a transgenerational pattern of clinical implication.